2017
DOI: 10.1016/j.biopsych.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Amylin Acts in the Lateral Dorsal Tegmental Nucleus to Regulate Energy Balance Through Gamma-Aminobutyric Acid Signaling

Abstract: Background The pancreatic- and brain-derived hormone amylin promotes negative energy balance and is receiving increasing attention as a promising obesity therapeutic. However, the neurobiological substrates mediating amylin’s effects are not fully characterized. We postulated that amylin acts in the lateral dorsal tegmental nucleus (LDTg), an understudied neural-processing hub for reward and homeostatic feeding signals. Methods We used immunohistochemical (IHC) and quantitative PCR analyses to examine expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 82 publications
3
31
0
Order By: Relevance
“…On a similar note, a recent clinical study investigating the effects of acamprosate on alcohol-dependent individuals attributed the drug's effects to calcium levels and not to a specific CNS target (Spanagel et al 2014). Nevertheless, a number of studies investigating the effects of locally administered sCT on food intake accompanied by immunohistochemistry data have identified central sites of action, especially in areas of the mesolimbic dopamine system (Mietlicki-Baase et al 2013;Mietlicki-Baase & Hayes 2014;Reiner et al 2017). Thus, we argue that the present findings do not fall under the scope of calcium levels regulation, but they are a result of sCT's central action.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On a similar note, a recent clinical study investigating the effects of acamprosate on alcohol-dependent individuals attributed the drug's effects to calcium levels and not to a specific CNS target (Spanagel et al 2014). Nevertheless, a number of studies investigating the effects of locally administered sCT on food intake accompanied by immunohistochemistry data have identified central sites of action, especially in areas of the mesolimbic dopamine system (Mietlicki-Baase et al 2013;Mietlicki-Baase & Hayes 2014;Reiner et al 2017). Thus, we argue that the present findings do not fall under the scope of calcium levels regulation, but they are a result of sCT's central action.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have presented that amylin receptor signalling in VTA, NAc and LDTg (Baisley & Baldo 2014;MietlickiBaase et al 2015b;Reiner et al 2017) is involved in the control of food intake. Albeit these areas are part of the cholinergic-dopaminergic pathway, which is well established as an important pathway involved in reward-related behaviours (Soderpalm & Ericson 2013), very little is known about the role of amylin receptor signalling within these areas in regard to artificial reinforcers, such as alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Biological Psychiatry , Reiner et al . (8) explore how this effect is mediated. A separate study from 2014 showed that among elderly people, plasma amylin positively correlated with cognitive health, even after controlling for other metabolic risk factors such as diabetes and hyperlipidemia (9).…”
mentioning
confidence: 99%